Hodnocení použitelnosti webových GIS aplikací - Addo-Donkoh, Grace (Univerzita Pardubice, 2023)
This thesis focuses on usability evaluation for web-based GIS applications. The aim is to propose a suitable evaluation procedure to evaluate the usability of web-based GIS applications managed by public administration authorities. In effect, ten public administration geoportals were selected, that is, Czech Republic, Poland, Germany, Slovakia, and Austria, along with their respective capital cities, Prague, Warsaw, Berlin, Bratislava and Vienna. Through extensive literature reviews, practical criteria were set and through a multicriteria decision making, suitable evaluation methods were chosen. A mixed methodology approach as well as a combination of user testing, think-aloud, and questionnaire were employed for the usability evaluation. The findings revealed critical issues, such as limited functionality, findability problems, English translation issues and inactive features. The geoportal of Berlin demonstrated the least usability, while that of Vienna emerged as the most usable among the evaluated geoportals.
Usability evaluation of Web-based GIS applications
Keywords: hodnocení použitelnosti; použitelnost; uživatelské testování; webový gis; geoportál; veřejná správa; usability evaluation; usability; user testing; web-based gis; geoportal; public administration